1944-1945 Programs for Postwar Social Security and Medical Care - Witte, Edwin E. (The Review of Economics and Statistics, 1945)
S OCIAL SECURITY and employment' are looked upon, in all Allied Nations and also in most neutral countries, as the keys to economic well-being in the postwar era. Improved labor standards, economic advancement and social are the economic objectives of the Atlantic Charter. All these terms are somewhat vague in meaning, but they express the hopes of hundreds of millions of people and are central in all postwar planning. Even while the war was in progress, considerable improvement was made in the social security legislation of many countries.2 This is not true of the United States, in which there was no social security legislation whatsoever on the national level during the five years between the enactment of the Social Security Act Amendments of I939 and the passage of the Servicemen's Readjustment Act (the G. I. Bill of Rights) in I944, except for the adoption of annual riders to appropriations acts which provided for freezing of the old-age insurance tax rates. Some advances were made in the states, particularly in the liberalization of unemployment compensation benefits. But the only law in this country which broke new ground was the Rhode Island Act of 194I for cash disabilitv benefits. In many other countries, in contrast, the war period brought forth much new social security legislation. The advances in this respect have been greatest in the Latin American countries. Very significant new social-security legislation also has been enacted in England, Canada, and Australia, while in New Zealand the comprehensive national health insurance and medical-care program adopted shortly before the outbreak of hostilities has been put into full operation. More important even than the new legislation are the comprehensive programs for social security which were developed during the war. Prior to I 944, such postwar programs were formulated and publicized in England, the United States, Canada, Australia, and South Africa all of them under governmental auspices.3 The most famous of these was the Beveridge Plan in England, which made its appearance late in I942.4 Beyond question, this has been the most widely-discussed social security program ever advanced anywhere in the world. In this country it has brought forth far more articles than were written about the Social Security Act during the entire year that this major American social security measure was in preparation and under consideration in Congress. Almost immediately after its publication, the